1974
DOI: 10.1021/ja00817a050
|View full text |Cite
|
Sign up to set email alerts
|

Linear relation between substituted pyridine lone pair vertical ionization potentials and pKa

Abstract: The cation exchange rates in cryptates may be obtained most conveniently from variable temperature 1SC nmr spectra of 1/1 cryptateligand mixtures (forthcoming report). Double probe 13C, 23Na nmr studies may provide detailed information on the electric effects produced by ligand structure, binding sites, ion pairing, and me-dium15 as well as on molecular tumbling. Complexes of other metal cations may also be investigated (lithium and cesium for instance).30 (30) The use of nitrogen-14 as the quadrupolar nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…Photoelectron spectra have been determined for imidazole (1), the substituted 1-methyl-(2), 2-methyl-(3), 1,2-dimethyl- (4), 1-acetyl- (5), and l-(trifluoroacetyl)imidazoles (6), and benzimidazole (7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photoelectron spectra have been determined for imidazole (1), the substituted 1-methyl-(2), 2-methyl-(3), 1,2-dimethyl- (4), 1-acetyl- (5), and l-(trifluoroacetyl)imidazoles (6), and benzimidazole (7).…”
Section: Resultsmentioning
confidence: 99%
“…7.v = -1.67ecNDO-7.50eV (1) Substituent effects on imidazole, 7V, and calculated SCF orbital energies, e, are provided in Table I for the x2 and x3 functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occupied frontier orbitals of pyridines have been identified as the nitrogen "lone pair" orbital, n r , with r symmetry, and the two orbitals, p S and p A , with p-symmetry. 91, 113 We have found that there is a statistically significant correlation between log K for the coordination of substituted pyridines and energy of the p S orbital, but no correlation with the energy of the n r orbital (where orbital energies were computed using a RHF/SCF ab initio method employing a MP2/6-31G** basis set); 106 this supports the notion that p-bonding effects are more significant than r-bonding effects in determining the strength of binding of pyridines by the ferrous centre in Fe(II)-N-AcMP8.…”
Section: Ligand Substitution Reactions-equilibrium Constants For Ferr...mentioning
confidence: 99%
“…The occupied frontier orbitals of pyridines have been identified as the nitrogen ''lone pair'' orbital, n r , with r symmetry, and the two orbitals, p S and p A , with p-symmetry [7,79]; p S has the correct symmetry for interaction with the metal orbitals. We have previously shown there is a linear relationship between the energies of n r and p S , determined by ab initio MO calculations, and the magnitude of log K III for the binding of substituted pyridines by Fe III NAcMP8, and concluded that both r and p bonding is important [7]; a re-examination of our data shows, however, that it is likely that the correlation observed for the r component is not statistically significant.…”
Section: Factors Affecting the Stability Of Complexes Between Pyridinmentioning
confidence: 99%